Concept Mapping and Education - Ullah, AMM Sharif (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The assimilation theory of verbal learning leads to meaningful learning wherein the learning outcomes take the form of concept maps-networks of some selected linguistic expressions and concepts. Concept-map-based education helps avoid rote learning, prepare content for effective on-ground and e-learning, and measure learning outcomes at the course, program, and institutional levels. As a result, it has been used at school, college, university, and professional levels. This book consists of five selected articles, providing insights into concept-map-based education, and will benefit students, teachers, and education managers.